Importance of self-management interventions in hypertension patients: a scoping review - Alfrina Hany; Kuswantoro Rusca Putra; Ratih Arum Vatmasari; Anisa Nadya Nafis; Aura Tasya Amalia; Edy Khamdani (PAGEPress Publications, 2024)
Hypertension is a prevalent chronic condition that requires effective self-management strategies for optimal control and complications prevention. Self-management interventions have become a crucial component in the management of hypertension. Therefore, this review aimed to determine effective self-management strategies for hypertensive patients. Articles were searched from four databases, namely Science Direct, Ebsco (MEDLINE), Proquest, Pubmed and Sage Journals based on PRISMA guidelines. The search included articles published in English between 2013 and 2022. A key term search strategy was adopted using "self-management interventions", "nursing interventions", "experimental study" and "hypertensive patients" to identify relevant studies. The results showed that self-management interventions have been proven to have positive effects on various aspects of hypertension self-management, including blood pressure monitoring, disease knowledge, medication adherence, and lifestyle modifications. These interventions can be delivered through technology-based platforms. Moreover, there are different types of self-management interventions for hypertensive patients, including individual and group approaches, the use of technology, nursing theory, and interventions based on the cultural aspects of patients. To conclude, as professionals, nurses should be able to determine which self-management strategies are suitable for the conditions and requirements of patients.